STUDENT ACTIVITIES IN ORGANIZING, LEARNING MOTIVATION AND SELF-ADJUSTMENT (CASE STUDY IN PTKIN STUDENTS) - Muhammad Buchori Ibrahim; Tarmidi Dadeh; Fasti Rola (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study focuses on the study of organizational activities with learning motivation moderated by self-adjustment variables. This study looked at the resulting influence between organizational activities and motivation to learn, then looked at the two variables mediated by self-adjustment. The perspective that students who are active in organizations are considered to have difficulty in maintaining their learning motivation, an analysis is carried out to see the influence that arises from this variable. The sample for this research was taken as many as 254 students from PTKIN in North Sumatra. This study uses a quantitative research approach with simple random sampling technique, respondent data is collected by filling out via google form and then the data is analyzed by mediation analysis and data analysis calculations assisted by JASP software, the validity test of the research scale is carried out by Confirmatory Factor Analysis. The prerequisite test was carried out with the results meeting the criteria, then a mediation analysis was carried out and the results of the analysis showed that self-adjustment was proven to be a mediating variable that connected organizational activity variables with learning motivation by 30.3% and there was a partial mediation effect and there were direct effects and indirect effects between these variables.Keywords: Organizational Activities, Learning Motivation, Adjustment, Students, Moderation of Adjustment.